Doping Effect on Conducting Polymer‐Metal Schottky DC Generators. (7th December 2018) - Shao, Hao; Fang, Jian; Wang, Hongxia; Zhou, Hua; Niu, Haitao; Chen, Fanyan; Yan, Guilong; Fu, Sida; Cao, Yuying; Lin, Tong
Abstract: Conducting polymer‐metal Schottky diodes show an interesting mechanical energy‐to‐electricity conversion ability to generate direct current (DC) power without rectification. However, little is reported about how dopants in conducting polymer affect the energy conversion behavior of Schottky diodes. In this study, a novel effect of dopants on mechanical energy‐to‐DC electricity conversion of conducting polymer‐metal Schottky devices is demonstrated. Using polyaniline (PANI) as a model, conducting polymers doped with a series of protonic acids is prepared. Without dopant, the device exhibits low mechanical‐to‐electrical outputs. Protonic acid doping enhances device energy conversion ability, and the dopant molecular dimension plays a significant part in deciding device performance. When HCl is used as dopant, the PANI device could produce peak outputs of 0.9 V and 33.9 µA cm −2 under compressive impact. These novel understandings foster the design of DC generators for various applications. Abstract : Dopant in conducting polymer shows significant effect on the power outputs of Schottky DC generators. The device with chlorine ion dopant has almost four orders of magnitude increase in electrical output compared to that without dopant in conducting polymer.